Benefit of delayed primary excision in rhabdomyosarcoma: A report from the Children's Oncology Group. Issue 2 (20th October 2020) - Lautz, Timothy B.; Chi, Yueh‐Yun; Li, Minjie; Wolden, Suzanne L.; Casey, Dana L.; Routh, Jonathan C.; Granberg, Candace F.; Binite, Odion; Rudzinski, Erin R.; Hawkins, Douglas S.; Venkatramani, Rajkumar; Rodeberg, David A.
Abstract : Background: Most children with intermediate‐risk rhabdomyosarcoma (RMS) have gross disease (group III) at the initiation of chemotherapy. Delayed primary excision (DPE) after induction chemotherapy allows for a reduction in adjuvant radiation dose, but with the risk of potential surgical morbidity. The objectives of this study were to compare outcomes in children with group III RMS who did and did not undergo DPE and to assess surgical morbidity. Methods: The study included 369 patients who had clinical group III RMS at sites amenable to DPE from intermediate‐risk Children's Oncology Group studies D9803 (encouraged DPE) and ARST0531 (discouraged DPE). Results: The primary tumor site was bladder/prostate (136 patients; 37%), extremity (97 patients; 26%), trunk (24 patients; 7%), retroperitoneum (91 patients; 25%), or intrathoracic/perineum/perianal (21 patients; 6%). In total, 112 patients (53.9%) underwent DPE in D9803, and 26 patients (16.2%) underwent DPE in ARST0531 ( P < .001), with loss of vital organ or function in 30 of 138 patients (22%). DPE allowed for a reduced radiation dose in 110 of 135 patients (81%; 51% were reduced to 36 Gy, and 30% were reduced to 42 Gy). Patients who underwent DPE had improved unadjusted overall survival ( P = .013). In adjusted regression analysis, the risk of death (hazard ratio, 0.71; 95% CI 0.43‐1.16) was similar for patients who did and did not undergo DPE and was improved for the subset of patients who had tumors of the trunk and retroperitoneum (hazard ratio, 0.44; 95% CI, 0.20‐0.97). Conclusions: Children with group III RMS have equivalent or improved outcomes with DPE and can receive a decreased radiation dose for definitive local control. The choice of local control modality should weigh the potential morbidity of surgery versus that of higher dose irradiation. Abstract : In this study of 369 children with group III rhabdomyosarcoma, 37% underwent delayed primary excision, allowing for a reduced radiation dose in 81% of patients. This approach resulted in overall equivalent outcomes compared with patients who received definitive radiotherapy and improved outcomes in the subset of patients with trunk and retroperitoneal tumors.